Story Power: Breathing Life into History - Manvell, Elizabeth C. (Rowman & Littlefield Publishers, 2011)
Not every teacher loves history and the same can be said about students. It doesn't have to be that way. People love a good story. History is a collection of stories that trace the path people, famous and little known, took as they faced the challenges of life. The choices they made teach us about human nature and help us better understand the world, each other, and ourselves. When students hear something interesting, something they connect to personally, they pay attention and want to know more. The stories in primary materials - a diary, letter, census record, photograph, official report - breathe life into history and invite critical thinking and conceptual understanding. Story Power! teaches us where to find stories, to assess the quality of sources, and to go past shallow summaries to the complicated story below the surface. Readers share in the author's personal journey beginning with discovery of Civil War letters, to piecing together the true story of the soldier's lives, and to a more complete understanding of America during the Civil War.